Tribocorrosion studies of metallic biomaterials: The effect of plasma nitriding and DLC surface modifications. (October 2016) - Zhao, Guo-Hua; Aune, Ragnhild E.; Espallargas, Nuria
Abstract: The medical grade pure titanium, stainless steel and CoCrMo alloy have been utilized as biomaterials for load-bearing orthopedic prosthesis. The conventional surgery metals suffer from a combined effect of wear and corrosion once they are implanted, which may significantly accelerate the material degradation process. In this work, the tribocorrosion performance of the metallic biomaterials with different surface modifications was studied in the simulated body fluid for the purpose of investigating the effect of the surface treatments on the tribocorrosion performance and eventually finding the most suitable implantation materials. The metals were subjected to surface modifications by plasma nitriding in different treatment temperatures or physical vapor deposition (PVD) to produce diamond-like carbon (DLC) coating, respectively. The dry wear and tribocorrosion properties of the samples were evaluated by using a reciprocating ball-on-disc tribometer equipped with an electrochemical cell. Prior to the tribocorrosion tests, their electrochemical behavior was measured by the potentiodynamic polarization in phosphate buffer saline (PBS) solution at room temperature. Both stainless steel and CoCrMo after low temperature nitriding kept their passive nature by forming an expanded austenite phase. The DLC coated samples presented the low anodic corrosion current due to the chemical inertness of the carbon layer. During the tribocorrosion tests at open circuit potential, the untreated and low temperature nitrided samples exhibited significant potential drop towards the cathodic direction, which was a result of the worn out of the passive film. Galvanic coupling was established between the depassivated (worn) area and the still passive (unworn) area, making the materials suffered from wear-accelerated corrosion. The DLC coating performed as a solid lubricant in both dry wear and tribocorrosion tests, and the resulting wear after the tests was almost negligible.